Prevalence and Impact of Chlamydia trachomatis Infection in Primary and Secondary Infertile Women of Kurdish Ethnicity in Erbil Provence- Iraq - Omer, Lawin A; Suhaila N. R. Darogha (Zanco Journal of Pure and Applied Sciences, 2024)
Chlamydia trachomatis is the predominant bacterium transmitted through sexual activity, usually leading to symptomless infection and complications like infertility. Therefore, it is crucial to have an efficient diagnostic technique to minimize the long-term consequences of the disease. A case-control study in which 4 ml blood samples and endocervical swabs were collected from 134 infertile and 50 fertile Kurdish women. DNA was extracted from endocervical swabs using PCR to detect C. trachomatis. Also, the serological test was performed using the enzyme-linked immunosorbent assay (ELISA) test to estimate anti-chlamydial IgM from serum. Among the study participants, we found that from 134 infertile participants, Women with secondary infertility showed a higher prevalence, 86 (64.1%), than primary infertility, 48 (35.8%). The overall prevalence of genital C. trachomatis, determined through PCR testing, was found to be 62 cases (46.2%) among infertile women. Among these cases, 21 individuals (33.8%) were diagnosed with primary infertility, while 41 individuals (66.1%) had secondary infertility. In contrast, there were no positives among the fertile group. All fertile and infertile female groups were positive for anti-chlamydial IgM antibody by using ELISA. Still, the intensity of response differed between cases, with the highest rate observed in unexplained infertility (UI) (71.42%), followed by endometriosis (Endo) (66.66%), tubal factor infertility (TFI) (50%), and polycystic ovarian syndrome (PCOS) (37.5%). These results highlight the importance of considering C. trachomatis as a potential factor in infertility cases. The results concluded the highest frequency of chlamydial infection was among women with infertility than fertile women. PCR is the most reliable and exact diagnostic method for detecting it.